Elastic shape memory polymeric materials for comfort fitting footwear - Wang, Taoxi (2019)
Nowadays consumers demand more and more comfort and functionality from their footwear, making these characteristics very important considerations in footwear design and evaluation. Both are the results between the nature of human body and different elements of the footwear. Although there are quite many different methods or ways to achieve better comfort fitting, for instance, via 3D printing, disadvantages are still quite obvious in available products in the market. Thus, in order to improve comfort fitting and provide a better solution to consumers, shape memory polymers are introduced. First, a commercially available polymer, namely ethylene-vinyl acetate (EVA) foam is investigated in terms of its shape memory effect (SME). It is concluded that this EVA foam can satisfy some but not all of the requirements for comfort fitting shoes. Since it is difficult to find an existing shape memory material that meets the requirements for comfort fitting footwear, both thermoset and thermoplastic shape memory hybrids (SMHs) programmable at around human body temperature with tailorable elasticity and stretchability are developed. The fitting time window for the thermoset version is over 10 minutes, while it is less than two minutes for the thermoplastic version. No similar materials have been reported so far. Additionally, some possible shoe designs are proposed and the enhanced stretchability via local structural design is investigated by finite element method (FEM). Subsequently, a few prototypes are fabricated and the feasibility to actualize comfort fitting shoes using developed materials is demonstrated. Although the shoe prototypes are only for the purpose of proof-of-concept, the demonstration successfully shows that the prototypes are deformable to fit different sized feet at around human body temperature. Such a kind of comfort fitting approach has yet been achieved using any other existing materials and technologies.